Optimal parameter estimation of permanent magnet synchronous motor by using Mothflame optimization algorithm / Abdolmajid Dejamkhooy and Sajjad Asefi - Dejamkhooy, Abdolmajid; Asefi, Sajjad (UiTM Press, 2018)
Precision of model parameters is vital in a permanent magnet synchronous motor high performance and controllability. Since these parameters are affected by different operation conditions and load changings, then an accurate estimation strategy is quite necessary. In this paper, stator resistance and disturbed load torque, which assumed to be variable, are estimated. For this purpose, optimal parameter estimation problem is constructed as a least squares one. In the next step, the parameter identification as an optimization problem is solved by Moth-flame optimization, which is a novel nature-inspired heuristic algorithm. Simulation results and their comparison with Particle Swarm Optimization based method show high performance and good ability of the proposed method in PMSM parameter estimation.